1997
DOI: 10.1097/00000441-199712000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Pancreatic β-cell Function in Hemochromatosis: Combined Treatment With Recombinant Human Erythropoietin and Phlebotomy

Abstract: A patient with diabetes mellitus caused by secondary hemochromatosis was treated using recombinant human erythropoietin and phlebotomy. A total of 12 g of iron had been infused in the patient because of iron deficiency anemia. Blood glucose level was 17.3 mmol/L, and hemoglobin A1c level was 9.0% at admission. He was treated using phlebotomy (400 mL per week), along with subcutaneous injection of 3,000 U of recombinant human erythropoietin three times a week. After approximately 100 days, a total of 5,500 mL o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…Thus far, two prospective studies using the sTfR:ferritin ratio as a marker of body iron stores found similar significant associations [9,10]. Use of phlebotomy or iron-chelation therapy to reduce ferritin levels was associated with improved glucose tolerance in patients with HH [44,45], healthy blood donors [46], patients with metabolic syndrome [47], and patients with T2DM [48]. These studies support our findings of a significant association between increased body iron stores and T2DM risk.…”
Section: Discussionmentioning
confidence: 95%
“…Thus far, two prospective studies using the sTfR:ferritin ratio as a marker of body iron stores found similar significant associations [9,10]. Use of phlebotomy or iron-chelation therapy to reduce ferritin levels was associated with improved glucose tolerance in patients with HH [44,45], healthy blood donors [46], patients with metabolic syndrome [47], and patients with T2DM [48]. These studies support our findings of a significant association between increased body iron stores and T2DM risk.…”
Section: Discussionmentioning
confidence: 95%
“…HH individuals have a 60% chance of developing T2D in their lifetime, compared to 35% in the general population [ 34 ]. Regular phlebotomy temporarily reduces circulating iron burden and blood glucose levels in HH subjects with T2D [ 35 ]. Mouse models of HH reveal that chronic iron overload decreases insulin secretion capacity due to high levels of oxidative stress [ 36 ].…”
Section: Dietary Iron: Too Much Of a Good Thing?mentioning
confidence: 99%
“…Iron reduction by phlebotomy and chelation therapy produced an improvement in glucose tolerance not only in patients with hemochromatosis (Dymock et al, 1972; Inoue et al, 1997), but also in healthy donors. Houschyar et al (2012) reported that reduction of body iron stores through phlebotomy had therapeutic effects in metabolic syndrome patients, including lowered blood pressure and improvement in glycemic control and cardiovascular risks.…”
Section: Iron and Metabolic Syndrome And Diabetesmentioning
confidence: 99%